2021
DOI: 10.1111/1467-8489.12446
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous impacts of information technology adoption on pesticide and fertiliser expenditures: Evidence from wheat farmers in China*

Abstract: This study examines the impacts of mobile information technology adoption on agrochemical expenditures, using data collected from 551 wheat farmers in China. Unlike previous studies that analyse a homogeneous relationship between the adoption of information technologies and farm input use, in this study, an instrumental variable quantile regression approach is utilised to capture the heterogeneous impacts of smartphone use on pesticide and fertiliser expenditures. Findings reveal that smartphone use affects pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 69 publications
(103 reference statements)
3
32
0
Order By: Relevance
“…By looking into the direct impact of rural broadband adoption on ACRE and its related moderating effect, this study has generated a rich set of empirical findings. Firstly, based on the EKC hypothesis and considering the role of broadband adoption, our econometric results confirm the hypothesis that rural broadband adoption has a positive role in promoting agricultural carbon emissions reduction, supporting that which was reported in the literature [32,45,46]. Then, through further analysis of the mediation effect of land transfer and farmers' investment in production equipment on ACRE, we found that the positive effect of broadband adoption on ACRE was more obvious when land transfer rates are high.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…By looking into the direct impact of rural broadband adoption on ACRE and its related moderating effect, this study has generated a rich set of empirical findings. Firstly, based on the EKC hypothesis and considering the role of broadband adoption, our econometric results confirm the hypothesis that rural broadband adoption has a positive role in promoting agricultural carbon emissions reduction, supporting that which was reported in the literature [32,45,46]. Then, through further analysis of the mediation effect of land transfer and farmers' investment in production equipment on ACRE, we found that the positive effect of broadband adoption on ACRE was more obvious when land transfer rates are high.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, broadband adoption can promote green agricultural production and achieve a significant improvement in ACRE. In terms of the positive impact of broadband adoption on the agricultural environment, our results were consistent with those by Ma and Zheng [46].…”
Section: Rural Broadband Adoption and Acresupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, let us describe U iA as the utility obtained by growers i from the adoption of MIT and U iN as the utility obtained from not adopting. Under this assumption, if the utility obtained from adopting the technology is larger than the utility of not adopting it, D * i = U iA − U iN > 0, and farmers usually adopt the technology [59][60][61][62][63]. Meanwhile, as these two utility values are unobservable, we could articulate them as function factors such as technical and farmer attributes in the latent variable model, as shown below:…”
Section: Modeling the Adoption Decision And Influencing Problemsmentioning
confidence: 99%
“…Some agronomists have suggested that the substitution of chemical fertilizers with organic soil amendments (e.g. organic fertilizers and farm manure) can help mitigate the adverse effects of chemical fertilizer usage 9 . Therefore, reasonable uses of chemical fertilizer and improvements of its efficiency are practical issues to be investigated globally.…”
Section: Introductionmentioning
confidence: 99%